2011
DOI: 10.1116/1.3554718
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of ultrathin AlN films for high frequency electroacoustic devices

Abstract: Articles you may be interested inSynthesis and characterization of 10nm thick piezoelectric AlN films with high c-axis orientation for miniaturized nanoelectromechanical devices Appl. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…High resolution TEM analyses have shown that these ultrathin fi lms have a fi ne columnar texture and a continuous lattice microstructure within a single grain from the interface with the Mo layer through to the AlN surface, thus confi rming the presence of a strong orientation even in the 25-nm-thick fi lm. 65 Preliminary characterizations of these ultrathin AlN fi lms performed in collaboration with Polytechnic University of Madrid (solidly mounted BAW resonators), 62 University of California-Berkeley (Lamb wave resonators), 68 and University of Pennsylvania piezoelectric nanoelectromechanical actuators) 10 , 69 validate the study's potential as a technological base by which to further increase operation frequency and overall performance of different types of electroacoustic devices.…”
Section: 67mentioning
confidence: 99%
See 2 more Smart Citations
“…High resolution TEM analyses have shown that these ultrathin fi lms have a fi ne columnar texture and a continuous lattice microstructure within a single grain from the interface with the Mo layer through to the AlN surface, thus confi rming the presence of a strong orientation even in the 25-nm-thick fi lm. 65 Preliminary characterizations of these ultrathin AlN fi lms performed in collaboration with Polytechnic University of Madrid (solidly mounted BAW resonators), 62 University of California-Berkeley (Lamb wave resonators), 68 and University of Pennsylvania piezoelectric nanoelectromechanical actuators) 10 , 69 validate the study's potential as a technological base by which to further increase operation frequency and overall performance of different types of electroacoustic devices.…”
Section: 67mentioning
confidence: 99%
“…65 Note that a smooth and well-textured bottom electrode is imperative for growth of highly c -axis oriented AlN fi lms. As a polar material with the wurtzite structure, an AlN fi lm with the c -axis perpendicular to the substrate can have two physical orientations of the columnar grains with the fi lm surface terminating in either the aluminum or nitrogen basal plane.…”
Section: Nanoscaled Aluminum Nitride Fi Lmsmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a) shows the essential fabrication process steps. In this device, the 650-nm thick AlN is deposited on 2-µm thick thermally grown SiO 2 on Si substrate using an S-gun magnetron sputtering system [45]. The deposited film has around ±75 MPa stress and high c-axis orientation.…”
Section: Low Loss Aln Device Fabricationmentioning
confidence: 99%
“…SHF applications require a remarkable reduction of the thickness of the AIN films to values for which their crystal quality and piezoelectric activity drop significantly [9], owing to the poor crystal quality of the material in the initial stages of growth. BAW resonators based on ultra thin AIN films (from 150 nm to 300 nm) are being developed in some research institutions and companies [1][2][3][10][11][12][13][14]. However, the crystal quality of such films is still far from that of thicker films.…”
Section: Introductionmentioning
confidence: 99%